Kinerja Teknik Transmisi OFDM melalui Kanal HAPS (High Altitude Platform Station) - Afriandi Ferdinan; Imam Santoso; Darjat Darjat (Transmisi: Jurnal Ilmiah Teknik Elektro, 2012)
Provision of broadband communications services in High Altitude Platform Station (HAPS) is a new idea and worthy to be discussed. One is the application of OFDM transmission technique as a medium for digital modulation in HAPS. HAPS is a new technology in the telecommunications sector at an altitude of 18-50 km (the stratosphere) and used to serve the broadband wireless access (BWA) and other multimedia devices. HAPS technology has advantages that can cover the lack of terrestrial and satellite technology. Performance of OFDM transmission technique in which a HAPS channel Rician channel can be evaluated by looking at the effect of K-factor. K-factor is the dominant signal power ratio (Line Of Sight) with multipath signal power. In real conditions on the ground, the received power is a combination of the dominant signal power and multipath signal power. The increase in elevation angle between the HAPS platform with user terminals resulted in the increasing value of K-factor and the influence that affected the performance of OFDM systems multipath fading. Effect of K-factor can be identified by computer simulation. Effect of K-factor observed by looking at the value of Bit Error Rate (BER) on the system to the value of signal to noise ratio (SNR) by varying the bitrate and frequency doppler. The results showed that the increasing value of K-factor at the same bitrate the smaller the resulting BER. This shows the better performance of OFDM systems. Meanwhile, the OFDM system performance deteriorated over increasing Doppler frequency. This is because the increasing value of K-factor at the same Doppler frequency resulting more BER value. Keywords: HAPS, OFDM, K-factor, BER, bit rate, Doppler frequency.